2005
DOI: 10.1007/s00270-004-0277-0
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotherapy for Simple Cysts with Use of Ethanolamine Oleate: Preliminary Experience

Abstract: We evaluated the efficacy of ethanolamine oleate (EO) as a sclerosing agent for a symptomatic hepatic or renal cyst. Seven patients with symptomatic hepatic (n = 3) or renal cysts (n = 4) were treated by sclerotherapy with EO. The cyst size in the greater diameter ranged from 6 to 13 cm. The cyst was punctured under ultrasound guidance, and after all of the cyst's content was aspirated, an iodized contrast agent was injected to check the absence of communication between the cyst and biliary tree, urinary tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 6 publications
1
41
1
2
Order By: Relevance
“…The emerging data (Table 3) [12,19,20,[23][24][25][26][27][28][29][30] suggest that sclerotherapy could be a viable alternative to open/laparoscopic deroofing of cysts. However, no randomized controlled trial comparing the two modalities exists to date, and the differing end-points reported by most studies make comparison of the two procedures difficult.…”
Section: Discussionmentioning
confidence: 96%
“…The emerging data (Table 3) [12,19,20,[23][24][25][26][27][28][29][30] suggest that sclerotherapy could be a viable alternative to open/laparoscopic deroofing of cysts. However, no randomized controlled trial comparing the two modalities exists to date, and the differing end-points reported by most studies make comparison of the two procedures difficult.…”
Section: Discussionmentioning
confidence: 96%
“…Monoethanolamine oleate (EO) sclerotherapy therapy was performed and reported by Yamamoto et al [11] in a small number of patients. We also performed the procedure for 17 cysts in 13 patients and previously reported a volume reduction rate of 93.3% and a recurrence rate of 0% [12].…”
Section: Introductionmentioning
confidence: 99%
“…This agent can also be administered extravascularly into cystic structures, thereby inducing an inflammatory response on the luminal surface of the cysts, resulting in the adhesion of the cyst walls [24]. This agent has been used successfully in adult medicine in the management of hydroceles [25] and in the sclerosis of various cystic structures [24,26]. …”
Section: Discussionmentioning
confidence: 99%